The Metallogeny of the Lubei Ni–Cu–Co Sulfide Deposit in Eastern Tianshan, NW China: Insights From Petrology and Sr–Nd–Hf Isotopes - Li, Ping; Liang, Ting; Feng, Yonggang; Zhao, Tongyang; Tian, Jiangtao; Li, Dahai; Li, Jian; Chen, Gang; Wu, Changzhi (Frontiers in Earth Science, 2021)
The Lubei Ni–Cu–Co deposit situated in western segment of the Huangshan– Jing'erquan mafic-ultramafic rock belt in eastern Tianshan of the Central Asian Orogenic Belt (CAOB). The estimated reserve is approximately 9.11 million tons of ore resources with average grades of 0.82 wt% Ni, 0.52 wt% Cu, and 0.03 wt% Co. The Lubei intrusion is mainly composed of gabbro (phase I), peridotite (phase II), pyroxene peridotite (phase III), olivine pyroxenite (phase IV), and diorite (phase V), which intruded into the early Carboniferous tuffaceous clastic rocks. Zircon Laser Ablation – Inductively Coupled Plasma – Mass Spectrometry (LA–ICP–MS) U–Pb age of the diorite (phase V) from the edge of the intrusion is interpreted as the top-limit metallogenic age, which is consistent with the formation ages of the Huangshan and Xiangshan Ni–Cu deposits in eastern Tianshan. The roughly parallel rare earth element (REE) curves of the Lubei intrusion indicate the magma originated from a homologous source. The slightly enriched large ion lithophile elements (LILE) are compared to high field strength elements (HFSE) with negative Nb and Ta anomalies show that the Lubei intrusion has arc-affiliate geochemical characteristics. The Sr–Nd-Hf isotopes show that the magma was derived from depleted lithospheric mantle, while suffering 4–10% lower crustal contamination with slight contamination of the upper crust. Based on a comprehensive conservation of regional geological, geochemical, and geochronological evidence, the primary magma of the Lubei intrusion was identified that it was derived from the partial melting of metasomatized lithospheric mantle previously modified by subduction events. The Lubei nickel–copper–cobalt sulfide deposit was formed after the primary magma experienced fractional crystallization, crustal contamination, and sulfide segregation in a post-collisional extensional geodynamic setting after the closure of the Kanggur ocean basin in the early Permian.